+0  
 
+1
68
1
avatar

 Pleassssse helppp me ASAP! I can only do this today,thank you

 Jan 8, 2020

Best Answer 

 #1
avatar
0

Here is a hint:

\(y=x^2-5x-6\) (1)

 

\(y=0x^2+2x-6\) (2)

 

Can you substitute (2) into (1)? 

 

Another hint, factor.

 

 

 

 

 

 

 

Solution:

\(2x-6=x^2-5x-6\)

Add 6

\(2x=x^2-5x\)

Subtract 2x

\(x^2-7x=0\)

Factor x

\(x(x-7)=0\)

x=0 or 7

Now substitute in both equation (1) and (2) to find y

\(y=x^2-5x-6=(7)^2-5(7)-6\) (1) equation

\(y=8\)

\(y=2x-6=2(0)-6\) (2) equation

y=-6

so the answer is first choice:

(7,8) & (0,-6)

 Jan 8, 2020
 #1
avatar
0
Best Answer

Here is a hint:

\(y=x^2-5x-6\) (1)

 

\(y=0x^2+2x-6\) (2)

 

Can you substitute (2) into (1)? 

 

Another hint, factor.

 

 

 

 

 

 

 

Solution:

\(2x-6=x^2-5x-6\)

Add 6

\(2x=x^2-5x\)

Subtract 2x

\(x^2-7x=0\)

Factor x

\(x(x-7)=0\)

x=0 or 7

Now substitute in both equation (1) and (2) to find y

\(y=x^2-5x-6=(7)^2-5(7)-6\) (1) equation

\(y=8\)

\(y=2x-6=2(0)-6\) (2) equation

y=-6

so the answer is first choice:

(7,8) & (0,-6)

Guest Jan 8, 2020

18 Online Users

avatar
avatar
avatar